Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Menggunakan Metode Profile Matching - DWI DANI APRIYANI (Faktor Exacta, 2021)
The calculation of scores that are still comprehensive for each student results in assessments that tend to be less objective. This has an impact on the selection of outstanding students which is less accurate and tends to be non-objective. This requires a decision support system for outstanding students. A decision support system using the profile matching method is one of the most frequently used methods because it can match criteria and has an accurate final decision. The weight criteria used are knowledge and skills, while the criteria for assessing outstanding students are report cards, learning attitudes, extracurricular activities, discipline, and attendance. With the existence of a decision support system for outstanding students, it is hoped that it can help teachers to be more objective in determining student achievement decisions.